Trait-like vulnerability of higher-order cognition and ability to maintain wakefulness during combined sleep restriction and circadian misalignment. Issue 8 (9th May 2019) - Sprecher, Kate E; Ritchie, Hannah K; Burke, Tina M; Depner, Christopher M; Smits, Alexandra N; Dorrestein, Pieter C; Fleshner, Monika; Knight, Rob; Lowry, Christopher A; Turek, Fred W; Vitaterna, Martha H; Wright, Kenneth P
Abstract: Study Objectives: Determine stability of individual differences in executive function, cognitive processing speed, selective visual attention, and maintenance of wakefulness during simulated sustained operations with combined sleep restriction and circadian misalignment. Methods: Twenty healthy adults (eight female), aged 25.7 (±4.2 SD ), body mass index (BMI) 22.3 (±2.1) kg/m 2 completed an 18-day protocol twice. Participants maintained habitual self-selected 8-hour sleep schedules for 2 weeks at home prior to a 4-day laboratory visit that included one sleep opportunity per day: 8 hours on night 1, 3 hours on night 2, and 3 hours on mornings 3 and 4. After 3 days of unscheduled sleep at home, participants repeated the entire protocol. Stability and task dependency of individual differences in performance were quantified by intra-class correlation coefficients (ICC) and Kendall's Tau, respectively. Results: Performance on Stroop, Visual Search, and the Maintenance of Wakefulness Test were highly consistent within individuals during combined sleep restriction and circadian misalignment. Individual differences were trait-like as indicated by ICCs (0.54–0.96) classified according to standard criteria as moderate to almost perfect. Individual differences on other performance tasks commonly reported in sleep studies showed fair to almost perfect ICCs (0.22–0.94). Kendall's rank correlations showed that individual vulnerability to sleep restriction and circadian misalignment varied by task and by metric within a task. Conclusions: Consistent vulnerability of higher-order cognition and maintenance of wakefulness to combined sleep restriction and circadian misalignment has implications for the development of precision countermeasure strategies for workers performing safety-critical tasks, e.g. military, police, health care workers and emergency responders.